Purification and Characterization of Fucoidan from the Brown Seaweed Sargassum binderi Sonder - ellya sinurat; Rosmawaty Peranginangin; Endang Saepudin (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2015)
The brown seaweed Sargassumsp. is well known as a source of fucoidan. Brown seaweeds found in Indonesia seas are dominated by Sargassum sp.The objectives of this research was to purify and characterize fucoidan from S. binderi Sonder. The fresh raw material was defatted by macerated in methanol:chloroform:water (4:2:1), filtered, rinsed with acetone and then air-dried in room temperature. The defatted dried seaweed was extracted with 0.01M HCl pH 4 at room temperature. Purification has been conducted using anion exchanger. The quality of fucoidan sample was determined for total sugar, functional group using FTIR, monomer content, total ash, and total sulfate in the ester form. The result shows that pure fucoidan contains fucose as the primary sugar component, and otherminor sugars (galactose, glucose, mannose and xylose). Chemical composition of crude fucoidan consisted of 74.25% fucose; 0.28% uronate acid; 10.29% sulfate and 5.5% protein. Purification using DEAE Sephadex A-25 gave 4 fraction pools yielding total sugar (%) of F1 (17.59); F2 (18.92); F3 (13.72); F4 (49.76), respectively. The components that build the fucoidan of S. binderi Sonder were estimated derived to be from fucoidan oligomers including (1,4)-L-FucS-Gal and D-(1,4)-Gal-GalS.